SPECIFICS OF LEGAL REGULATION OF MECHANISMS OF PUBLIC-PRIVATE PARTNERSHIPS’ FORMING IN THE RUSSIAN FEDERATION - S. Pospelov (Вестник университета, 2017)
Development of mechanisms of the public-private partnership (PPP) in Russia promoted enhancement of its legal regulation. At the same time, there is a number of unresolved problems in the plan of a regulation of measures and instruments of regulation of interaction of the state and business. In the article the analysis of the modern Russian legislation in the context of regulation of PPP is carried out, its benefits and shortcomings are revealed.